Methodological choices in size and density fractionation of soil carbon reserves – A case study on wood fiber sludge amended soils - Keskinen, Riikka; Nikama, Johanna; Kostensalo, Joel; Räty, Mari; Rasa, Kimmo; Soinne, Helena (Elsevier, 2024)
Soil organic carbon (SOC) is in the focus of research due to its central role in regulating climate and maintaining fertility and resilience of soils. Methodologically, shifting from whole soil C measurements to specific SOC fractions increases possibility to detect small changes in the vast SOC storage, and enhances estimation of SOC stability. However, SOC fractionation schemes are numerous and variable. In this study, deionized water and sodium hexametaphosphate (SHMP) were compared in soil dispersion by separating soils into coarse (0.25–2 mm), medium (0.063–0.25 mm) and fine (<0.063 mm) size fractions. The first two fractions were further separated by density (1.8 g cm−3) to obtain free particulate organic C (POC) and mineral associated organic C (MOC). The approach was applied to a clay and a silt loam soil with and without wood fiber sludge amendment to follow the added C. Aggregate disruption was enhanced with SHMP in comparison to water, but the effect was small and the use of SHMP decreased recovery of SOC, wherefore water was preferred. In both soils, 5–10 % of SOC occurred as coarse POC, 1–3% as coarse MOC, 5 % as medium POC, 10 % as medium MOC, and 70–85 % as fine MOC. The added C resided in the POC fractions with an indication of minor accumulation to the fine MOC in the clay soil. Longer time frame with repeated C additions would be needed to increase the stable MOC storages though saturation of the MOC reserve may hinder accumulation in the silt loam low in fines.
Keywords: Organic amendments; Soil conditioning; Carbon storage; Method development